Humeral stem loosening following reverse shoulder arthroplasty - systematic review and meta-analysis - Grey, Barend Christiaan (Department of Health and Rehabilitation Sciences, 2017)
Background: Aseptic stem loosening following reverse shoulder arthroplasty (RSA) is an uncommon complication. The majority of literature on RSA consists of case series with short follow-up periods. It remains unknown which factors contribute to aseptic stem loosening in RSA. Our analysis aimed to compare the incidence of aseptic stem loosening, humeral radiolucent lines (RLL) and revision for stem loosening between: 1) cemented and uncemented stems, and 2) different etiological subgroups Methods: In a systematic review 75 articles were included after assessment of study methodology and a meta-analysis of 1660 cemented and 805 uncemented stems was performed. We compared the incidence of aseptic stem loosening, humeral RLL, and revision for stem loosening between: 1) cemented and uncemented stems from cohorts with short (< 5 years) mean follow-up periods, long (≥ 5 years) mean follow-up periods, and all cohorts combined; and 2) different etiological subgroups. Results: The overall incidence of aseptic stem loosening was 1%. When comparing cemented to uncemented stems, there was no significant difference in the incidence of aseptic stem loosening or of revision for stem loosening in both the short and long term follow-up groups. Humeral RLL were more common with cemented stems (15.9% versus 9.5%, p = 0.002). The highest incidence of aseptic stem loosening occurred in the tumor subgroup (10.81%), followed by RSA as revision for failed arthroplasty (3.66%). No stem loosening was seen in the acute fracture or fracture sequelae groups. Conclusion: Aseptic stem loosening occurred more commonly in cohorts with long follow-up times (2% vs 0.8%, p = 0.01). There was no difference in the incidence of aseptic stem loosening or revision for stem loosening between cemented and uncemented stems. Humeral RLL occurred more frequently when cemented stems were used. Patients treated with RSA following excision of proximal humerus tumors and RSA as revision for failed arthroplasty were at greater risk of aseptic stem loosening.